2021
DOI: 10.1044/2021_jslhr-21-00142
|View full text |Cite
|
Sign up to set email alerts
|

Speech Development Between 30 and 119 Months in Typical Children I: Intelligibility Growth Curves for Single-Word and Multiword Productions

Abstract: Purpose We extended our earlier study on normative growth curves for intelligibility development in typical children from 30 to 119 months of age. We also determined quantile-specific age of steepest growth and growth rates. A key goal was to establish age-specific benchmarks for single-word and multiword intelligibility. Method This cross-sectional study involved collection of in-person speech samples from 538 typically developing children (282 girls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…One explanation for this difference is that children in the higher percentiles begin with faster articulation rates and therefore do not have as far to advance before becoming adultlike. This same phenomenon was observed in our companion study of speech intelligibility (Hustad et al, 2021).…”
Section: Overall Growth In Articulation Rate Between 2 and 9 Yearssupporting
confidence: 85%
See 2 more Smart Citations
“…One explanation for this difference is that children in the higher percentiles begin with faster articulation rates and therefore do not have as far to advance before becoming adultlike. This same phenomenon was observed in our companion study of speech intelligibility (Hustad et al, 2021).…”
Section: Overall Growth In Articulation Rate Between 2 and 9 Yearssupporting
confidence: 85%
“…The companion study focusing on speech intelligibility development (Hustad et al, 2021) All children were from the upper midwestern region of the United States, and their demographic characteristics reflect those of Wisconsin. Table 1 shows demographic information for the children.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until very recently, comprehensive normative standards for characterizing intelligibility development in typical children did not exist. The most recent work, however, has provided a foundation for understanding growth trajectories between the ages of 2 and 10 years [ 8 , 9 , 10 ]. Results have indicated that children’s intelligibility grows rapidly in the preschool years and is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Results have indicated that children’s intelligibility grows rapidly in the preschool years and is highly variable. Intelligibility continues to improve with age throughout middle childhood, and variability decreases with age [ 8 , 9 , 10 ]. Studies of typical speech intelligibility development provide an important foundation for interpreting intelligibility in children with dysarthria.…”
Section: Introductionmentioning
confidence: 99%